Linguistic and cultural relations in the terminological system of the term "tourism" in English and Uzbek - Dildora Kholboyeva (Global Scientific Publishing, 2023)
In this work, the author examines Synonymy of terms, that is, the problem of using several special lexical units to designate one concept remains one of the main and most important problems of terminology.
Keywords: tour; terminology; concepts